Towards Integrated Engineering Curricula: South African Case Studies in Context with UCL’s IEP Approach - Smith, Lelanie; Tilley, Emanuela; Mitchell, John; Swartz, Bronwyn; Wolmarans, Nicky; Hattingh, Teresa (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Engineering education in South Africa faces persistent challenges, including diverse student preparedness, limited resources, and high dropout rates. This paper presents a project that responds by supporting national curriculum transformation through integrated learning approaches that embed both technical and professional competencies. In collaboration with University College London (UCL) and 16 South African universities, the project explores how global models can inform local curriculum design without direct replication. This paper examines four institutional case studies using Harden’s (2000) integration ladder and Fogarty’s (1991) curriculum integration models to map intended and actual integration practices. The frameworks offered a structured tool for comparative reflection and opened up strategic conversations about future directions. However, several limitations were noted: the models do not fully accommodate the interdisciplinary nature of engineering, assume a linear progression not always observed in practice, and focus on individual teaching rather than program-level design. Despite these challenges, the mapping process helped leaders of the four case study institutions herein critically reflect on where they are, where they intend to go, and how integration frameworks could evolve to remain relevant in diverse and complex educational contexts.